LIFESTYLES AND OBESITY IN YOUNG STUDENTS IN HIGHER EDUCATION - Silva, Armando Manuel Marques (2013)
Introduction: Lifestyles and obesity are characteristicsin our society that lead young people to situations of potential cardiovascular risk. Objectives: To characterize the lifestyle and to evaluate its relationship with body mass index in university students. Methods: This is a quantitative descriptive and cross-correlated study with a non-probability convenience sample of 3459university students in the Central Region of Portugal. The evaluation protocol includes a sociodemographic questionnaire, the scale of "Do You Have a Fantastic Lifestyle" in the portuguese version (Silva, Brito, Amado, 2011) and an auto-related Body Mass Index. Results: Regarding the sample, 69.6% were female students and 30.4% male.In terms of global results: Lifestyle behavior point averages medium level of 85.81±13.06; relative to variableBMI: 7.1% were underweight and 75.4% were normal weight, 14.3% were overweight and 3.2% obese.Regarding the correlations made between the two variables, we found significant correlations betweenGlobal lifestyle and the BMI (p=0,000), and some specific lifestyle domains, including: Family/Friends (p=0,000), Nutrition (p=0,000), Tobacco (p=0,007), Alcohol and other drugs (p=0,000) and Physical Activity (0,003). Conclusions: This study revealed a group of data that will help us define an intervention program pertaining to the promotion of health, such as: an increase in health related literacy or the development of student support groups where the educative community and health services are mobilized.